PERKEMBANGAN PENDIDIKAN ISLAM DI CINA - St. Aisyah Abbas (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
This article discusses the development of Islamic education in China using a historical approach. The results of the discussion obtained an understanding that the earliest Muslim communities in China were descended from traders, militias, and Muslim officials from Arab, Persian, Central Asian, and Mongolian origin who originally settled along the southeast coast of China in the 7th century AD although At first Muslims were considered foreigners, but because of their ability to communicate persuasively and assimilate with Chinese society, Islam was accepted by the Chinese peacefully and voluntarily, even some dynastic officials in China and other tribes embraced Islam. Then they built a mosque in every settlement of Chinese Muslims. Islamic education in China is developed through education in mosques, known as the "Mosque educational system" which was pioneered by Hu Deng Zhou, a Muslim scholar in the Xi'an area, and assisted by Ahong (Imam) as the main teacher at each mosque in China. The mosque thus has a long history, and is the oldest religious educational institution in China. Mosques in China during the early days of the growth of Islam in China, became the most important educational institutions. In addition to educational institutions in mosques, Islamic schools have also developed in China (a kind of madrasah / pesantren), both those placed on the porch of mosques and those managed by Islamic organizations. And for higher education, the government together with Chinese Muslims has established 9 (nine) Islamic universities, which are spread across various provinces.